Factors related to picky eating in toddlers: A scoping review - Candrasari, Amilia; Lestari, Retno; Hayati, Yati Sri (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2025)
Background: Eating problems are common among children, with approximately 25%-40% of toddlers being picky eaters. During the toddler developmental stage, children experience significant growth processes, and the role of the mother is crucial in ensuring that children are not exposed to nutritional deficiencies. Children's eating patterns begin to form before the age of 3 Many parents and children find this eating skill difficult. Objectives: This study aims to identify the factors associated with the prevalence of picky eating behaviours in toddlers. Methods: This study employs a systematic review approach, conducting a literature search across three databases: Google Scholar, ProQuest, and PubMed. The selection of articles is guided by the PRISMA Flowchart, followed by critical appraisal utilizing the Joanna Briggs Institute (JBI) instrument. The findings indicate that 15 articles relevant to the literature review were identified based on the established inclusion criteria.Results: Upon analyzing the literature, this study concludes that the factors influencing picky eating behaviours are attributed to external factors, specifically parental behaviours, and internal factors related to the child's behaviour. Picky eating, defined as selective eating behaviour, is a prevalent issue often observed in toddlers. This phenomenon can lead to growth disorders and may adversely impact children's nutritional status and overall health in the long termConclusions: Several factors influence the phenomenon of picky eating in children, the most prevalent being insufficient maternal knowledge and the demands placed on working mothers. This phenomenon can lead to growth disorders and may adversely impact children's nutritional status and overall health in the long term.